Integrated Modeling of Renewable Energy Penetration in Nigeria’s Power Grid: Technical, Economic, and Infrastructural Pathways for System Flexibility and Stability - Unegbu, Hyginus Chidiebere Onyekachi; YAWAS, Danjuma (Jurnal Pengabdian KOLABORATIF, 2026)
Nigeria’s electricity sector faces growing challenges in meeting rising energy demand while advancing climate commitments and ensuring long-term energy security. This study develops an integrated modeling framework to assess the technical, economic, and infrastructural implications of high renewable energy penetration in Nigeria’s power grid. Combining long-term energy planning using the Long-range Energy Alternatives Planning (LEAP) system, short-term economic dispatch modeling via PLEXOS, and power flow simulations through OpenDSS, the analysis evaluates three grid development scenarios: Business-As-Usual (BAU), Intermediate Renewable Energy (RE), and High Renewable Energy (RE) integration. The results demonstrate that increasing the share of solar and wind generation to 60% significantly lowers total generation costs, from $3.1 billion under BAU to $2.18 billion in the High RE scenario, while reducing CO₂ emissions by over 60%. Battery energy storage systems (BESS) and demand-side management (DSM) were found to be essential enablers of system flexibility, reducing curtailment and unserved energy, and improving peak load balancing. Voltage stability improved markedly with the deployment of inverter-based control and distributed storage, achieving over 97% compliance with voltage limits in the High RE scenario. Regional integration through the West African Power Pool (WAPP) further enhanced system performance and delivered net trade benefits. The study concludes that Nigeria’s grid can accommodate high renewable energy shares without compromising technical reliability or economic efficiency. These findings offer critical insights for policymakers and energy planners, emphasizing the need for regulatory reform, targeted infrastructure investments, and regional cooperation to achieve a sustainable and resilient energy future.
Keywords: Economic Dispatch Modeling; Economic Efficiency; Electricity Sector; Power Grid; Renewable Energy